Avaliação dos resultados neonatais do método canguru no Brasil - Lamy Filho, Fernando (2008)
Objective: To evaluate the results of the kangaroo mother method in Brazil. Methods: A prospective cohort study comparing 16 units that have or do not have the second phase of the kangaroo mother method: eight were national centers of excellence for the kangaroo mother method (study group) and eight were part of the Brazilian Neonatal Research Network (control group). A total of 985 newborn infants with birth weights of 500 to 1,749 g were enrolled. Multivariate analyses employedmultiple linear regression and Poisson regression with robust adjustment. Results: The adjusted analysis (controlled for birth weight, gestational age, Score for Neonatal Acute Physiology Perinatal Extension II, Neonatal Therapeutic Intervention Scoring System, and maternal age and educational level) demonstrated that mean length of hospital stay (p = 0.14) and intercurrent clinical conditions in the intermediate or kangaroo unit were equal for both groups. Weight (p = 0.012), length (p = 0.039) and head circumference (p = 0.006) at 36 weeks' corrected gestational age were all lower at the kangaroo units. The kangaroo units exhibited superior performance in relation to exclusive breastfeeding at discharge (69.2 vs. 23.8%, p=0.022). Conclusions: The evidence suggests that the humanization strategy adopted by the Brazilian Ministry of Health is a safe alternative to conventional treatment and a good strategy for promoting breastfeeding. Copyright © 2008 by Sociedade Brasileira de Pediatria.